THE INFLUENCE OF PROBLEM POSING AND MISSOURI MATHEMATICS PROJECT (MMP) ON LEARNING MATH LEARNING OUTCOMES REQUIRED FROM COGNITIVE STYLE - Selvi Rizki Kalintina; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Mathematics learning in class VIII SMPN 1 Kasihan Bantul academic year 2017/2018 using Problem Based Learning (PBL) learning model, which resulted in students still difficulty solving problems given by teachers so that teachers still guide students in solving the problem by giving its settlement step. As well as in learning, students lack confidence in conveying ideas or opinions. The use of a less precise learning model made the students less understood with the material described by the teacher and resulted in poor learning outcomes. This study aims to determine the effect of cognitive style on learning outcomes, the influence of the learning model of problem posing and MMP learning model on learning outcomes, and the interaction effect between cognitive style and problem-posing model and MMP on learning outcomes. This study's population is the student's class viii State Junior High School     (SMP N) 1 Kasihan Bantul consisting of 5 classes. Samples of 2 classes with the number of 63 students taken with random sampling technique to the class obtained VIII D as experimental class A and class VIII E as experimental class B. Research instrument in the form of Group Embedded Figures Test (GEFT) test, initial ability test, and test result learning. Data analysis used a two-way analysis test of variance analysis. Based on the first hypothesis test with a significance level of 5% and the value of FA = 5,05 while F0,05; 1,59 = 4,004 mean FA> Ftabel, indicating that there is the influence of cognitive style to result learn. The second hypothesis test with a 5% significance level and FB value = 3.70 while F0,05; 1,59 = 4,004 mean FB <Ftabel, indicating no effect of learning model of problem posing and Missouri mathematics project (MMP) model of outcome learn. The third hypothesis test with the cell is not equal to a 5% significance level and FAB value = 4.40, whereas F0,05,1,59 = 4,004 means FAB> Ftabel interaction between cognitive style and learning model to learning result.